Preventable Deaths among HIV-Positive Patients: A Real-Life Perspective from a Teaching Hospital in Northern Mexico - Andrea Ramirez Fontes; Juan Carlos Rodriguez Aldama; Luis Antonio Sanchez Lopez; Samantha Flores-Treviño; César Adan Almendarez-Sánchez; Adrian Camacho Ortiz (HIV/AIDS Research and Treatment-Open Journal, 2018)
Introduction Antiretroviral therapy (ART) in patients infected with human immunodeficiency virus (HIV) are more effective and better tolerated and for this reason the gap between life expectancy of an HIV-seropositive individual and a seronegative one has been closing. This study was carried out to identify the main causes of death in in HIV-infected patients in a tertiary-care hospital as well as relevant sociodemographic and clinical factors that contribute to their prognosis. Aim The aim of the present study is to identify the main causes of death in HIV/AIDS patients as well as relevant sociodemographic and clinical factors that contribute to their prognosis. Methods A retrospective cohort was conducted with confirmed HIV-infected adult patients who died between January 2010 and January 2017. Sociodemographic and clinical data were taken from their clinical records to carry out a statistical analysis on the mortality of these patients and the relevant factors that contributed. Results A total of 120 patients with in-hospital mortality and HIV diagnosis were included, of these, 55% were allocated to an AIDS defining event, 75.8% had an HIV diagnosis of less than 6 months from their death, 88.3% received HIV testing for suspicion or confirmation of an AIDS defining event, and 50% had two or more active AIDS defining events at admission. Conclusion A major public health concern is a late HIV/AIDS diagnosis, a situation that is occurring in Mexico. Despite universal access to antiretroviral treatment, the most common causes of mortality in HIV-positive patients are still AIDS defining events, mainly tuberculosis and other opportunistic infections that with a prompt diagnosis might have been prevented if these patients had initiated early antiretroviral therapy.